Family resilience of stroke survivors within 6 months after a first-episode stroke: A longitudinal study - Zhang, Wei; Zhou, Wanqiong; Ye, Mingming; Gao, Yitian; Zhou, Lanshu (Frontiers in Psychiatry, 2022)
Context Family resilience is frequently recognized as a powerful determinant of family adaptation in chronic disease patients; understanding the family resilience of stroke patients and its predictors could help nurses develop interventions to assist patients in maintaining healthy family functioning. Objective This study aimed to explore the trajectory of family resilience in the 6 months following stroke onset and examine the predictors of family resilience over time. Methods A total of 288 first-episode stroke survivors were selected from seven hospitals in China from July 2020 to March 2021. Their family resilience, social support, self-efficacy, and medical coping style were assessed at hospitalization and 1, 3, and 6 months after stroke onset. The study was performed in accordance with the STROBE guidelines. Results The mean levels of family resilience were between 95.52 ± 11.10 and 97.68 ± 9.68 within the first 6 months after a first-episode stroke, with a significant increase 3 months after the onset. Patient self-efficacy, social support, family atmosphere, and caregiver-patient relationship (sibling) were predictors of family resilience at all four time points. Baseline predictors of family resilience at 6 months included self-efficacy of the patients, subjective support, support utilization, family atmosphere, living district, medical bill payment methods, and caregiver-patient relationship (sibling). Conclusion Family resilience levels were low in stroke patients 6 months after the onset, and 3 months post-stroke onset was a critical period for family resilience of stroke patients. Nurses are recommended to pay particular attention to patients with low self-efficacy, perceived low support, poor utilization of available support, as well as those who are under the care of their siblings, self-pay, or live in a poor family atmosphere. Interventions aimed at improving the self-efficacy of patients and social support are potential approaches to enhance family resilience.